Interprofessional Collaboration and Involvement of Parents in the Management of Painful Procedures in Newborns - Balice-Bourgois, Colette; Zumstein-Shaha, Maya; Simonetti, Giacomo D.; Newman, Christopher J. (Frontiers in Pediatrics, 2020)
Introduction: Newborns are subject to many painful procedures. Pharmacological and non-pharmacological approaches alone are not enough, and it is necessary to consider other contributing elements such as the environment, interprofessional collaboration and parental involvement. The aim of this study, using Craig’s Social Communication Model of Pain as a framework to understand pain, was to explore interprofessionality and the role of parents to improve the management of painful procedures in newborns. Materials and methods: a pre-post feasibility study using a mixed method approach was conducted. Questionnaires, interviews and focus groups were used to describe the parents' views on their child's pain management and involvement in care as well as to explore the level of interprofessionality and feasibility. Results: Collaboration between physicians and nurses improved following the implementation of a complex interprofessional intervention involving professionals, parents and newborns. In spite of improving professional collaboration in procedural pain management, parents were attributed a passive role or only marginally involved in in the infant's pain management. However, parents stated – as elicited by the questionnaires and interviews – that they wished to receive more information and be included in painful procedures executed on their infant. Discussion: Management of painful procedures in neonates needs to be changed. Interprofessional collaboration contributes to improved procedural pain management in neonates. It is essential to include parents as active members in the interprofessional healthcare team.